Influence of organizational climate on job satisfaction and commitment of employees in innovative small-scale business - MS. B. NEERAJA,; PATHAK, MR. B. KRISHANAKANTH (The journal of contemporary issues in business and government, 2020)
Climate consists of a collection of features that define an organization, differentiate it from other relatively long-term organizations and influence the actions of people in it.. The purpose of this article is to present, by using ability of a model, the determinants of organizational way of life which influence creativity and innovation and to check whether or not a relationship existed between the variables job delight and organizational tradition of personnel within a service organization. The populace is collected from thermal power plant industry, and the data is collected from all levels of management (low, middle, top-level) 200 personnel of which fifty had been excluded from the research because of low levels of literacy.. The relationship between creativity, innovation and way of life is discussed in this context. Against the history of this model, the determinants of organizational culture were identified. The determinants are strategy, structure, support mechanisms, commitment, and job satisfaction, behavior that encourages innovation, organizational climate and open communication. The impact of every determinant on creativity and innovation is discussed. Values, norms and beliefs that play a position in commitment and job satisfaction can both support or inhibit creativity and innovation depending on how they have an effect on character and employees’ performance and behavior. This is additionally defined in this article.